Acompanhamento e avaliação de equipes docentes: estudo de caso dos cursos de nível superior da Universidade Federal de Alagoas no contexto da UAB - Valério, Liliane Cristine Moreira (2016)
This study aimed to verification of administrative strategies and repertoires used for overall coordination in the monitoring process and evaluation of the performance of teaching staff, including teachers and teachers-tutors of higher education at the Universidade Federal de Alagoas (UFAL) in framework of the Universidade Aberta do Brasil (UAB). The Information was collected by the nineteen coordinators of higher education distance education, making a sample equivalent to over 86% of the entity's coordinators. It was used the quantitative and qualitative research method, a descriptive approach, a case study, which was applied a semi-open questionnaire with sections created for observation data on the formation of the course coordinator and routines management performed in their daily lives. The research was developed from a central question that supposed to be a need to identify and map the administrative repertoires used by the general coordination of higher education distance education so as to allow viewing of good theorized management practices and applied under the UAB / UFAL. This research used data analysis technique for using the triangulation of data collected. It was based on the significant assumption confluence of themes inherent to education and administration in that sense, it is observed that the knowledge and experience derived from the theories of scientific management have important practical and repertoires for the operation and management of distance education, is at the top level or in other educational segments. The results of this study indicate that the analyzed coordination flexibly adopt the managerial repertoire pertaining to the universe of management theory concerning the subsystem of human resources at distance, signaling aspects of fragility and / or consolidation of theoretical assumptions relating to the topic.